INTERDEPENDENCE OF INTERNATIONAL TRADE AND MIGRATION IN A GLOBALISING ECONOMY: THE EVIDENCE FROM NIGERIA (2013)
The connection between trade and emigration has received increased attention in the literature. It has been shown that trade barriers and lack of adequate technology contribute to low exports and high imports of developing countries. This partly explains their high unemployment rate which, by implication, generates tendency to emigrate. Also, remittances from emigrants tend to increase imports. Although, researchers have investigated various aspects of trade, the connection between it and emigration has been generally neglected. This study examined the relationship between trade and emigration in Nigeria covering the period between 1980 and 2010. A gravity model, based on a modified Hecsher-Ohlin framework, was employed to estimate the trade-emigration relationship between Nigeria and five of her major trading partners – United States (US), United Kingdom (UK), Sweden, Italy and Canada. Three-level analyses were carried out in order to gain a deeper insight into trade-emigration relationship as follows: Nigeria and the trading partners as a group, Nigeria and each of the countries, and product-based (agricultural goods, textiles, food and beverages, chemicals, manufactures and petroleum products). Data were sourced from the World Integrated Trade Solution (WITS) and World Development Indicators (WDI). The Arellano-Bover System Generalized Method of Moments estimation technique was used to check simultaneity and endogeneity problems, while the Sagan tests of over-identifying restrictions were carried out to validate the instrumental variables used. All estimates were set at 5% level of significance. Emigration was negatively associated with exports (-0.20) and positively associated with imports (0.03). The export elasticities of emigration to Canada, US and Sweden were positive with 0.47, 0.27, and 3.90 coefficients respectively. Emigration responded positively to changes in imports from these countries with their corresponding coefficients respectively being 0.39, 0.2 and 1.58. Exports to Italy and UK were negatively related to emigration with an estimate of -3.90 and -0.09 respectively, while import elasticities of emigration from these countries were negative with estimates of -1.58 and -0.11 respectively. Exports of agricultural products, textiles and food and beverages to Canada, UK and US were negatively associated with emigration. Increases in emigration to these countries were associated with increases in imports of manufactured products, food and beverages and chemicals with coefficients ranging from 0.02 to 0.76. However, increases in emigration were associated with decreases in imports of agriculture and textiles products with respective estimates ranging from -1.05 and -0.01. Agriculture, textiles, and food and beverages export elasticities of emigration were, to Italy (0.02, 0.67, and 0.05) and to Sweden (1.91, 0.03 and 1.28). Manufactured import elasticities of emigration to these countries were -0.54 and -0.33 respectively. There is a strong connection between trade and emigration in Nigeria. Declining exports and rising imports was associated with increased emigration. Declining exports and rising imports of food and beverages, textiles and agricultural products partly accounted for increased emigration. Increase in manufactured goods, and chemical were associated with decrease in emigration. Government should therefore adopt policies that stimulate exports and moderate imports.